Expression profile of miRNAs computationally predicted to target PDL-1 in cervical tissues of different histology groups - Leventakou, Danai; Gouloumi, Alina-Roxani; Spathis, Aris; Pouliakis, Abraham; Koufopoulos, Nektarios; Pergialiotis, Vassilios; Drakakis, Peter; Panayiotides, Ioannis G.; Kottaridi, Christine (Frontiers in Cell and Developmental Biology, 2023)
Background: Human papilloma virus (HPV) is considered a successful pathogen as it has the ability to evade host immune responses and establish long-term persistent infection. It has been reported that programmed death ligand 1 (PDL-1) expression is correlated with HPV-positivity and is increased with lesion progression or tumor metastasis in cervical cancer. The expression of microRNAs (miRNAs) is often deregulated in cancer, and their potential targets are affected. Methods: RNA was extracted from formalin-fixed paraffin-embedded (FFPE) cervical samples of different histological types, previously typed for the presence of HPV. A specific quantitative polymerase chain reaction (qPCR) protocol with SYBR Green was used to check for the expression of four miRNAs that were computationally predicted to target PDL-1. Results and conclusion: hsa-miR-20a-5p and hsa-miR-106b-5p showed an expression increase with the severity of the lesions, while hsa-miR-125b-5p depicted a significant decrease in its expression in cancerous samples when compared to normal samples.